2006
DOI: 10.1111/j.1600-6143.2006.01362.x
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Based Combination Anti-Viral Therapy for Hepatitis C Virus After Liver Transplantation: A Review and Quantitative Analysis

Abstract: Recurrence of hepatitis C virus (HCV) infection after liver transplantation (LT) is universal.However, the efficacy, tolerability and safety of combination interferon and ribavirin (IFN-RIB) or peginterferon and ribavirin (PEG-RIB) anti-viral therapies post-LT are uncertain. We performed a comprehensive search of major medical databases and conference proceedings (1996-2005). The main outcome measure was sustained virological response (SVR, undetectable HCV RNA) at 6 months. Summary estimates were calculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
158
1
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(170 citation statements)
references
References 67 publications
7
158
1
4
Order By: Relevance
“…In uncontrolled studies the combined use of pegylated interferon and ribavirin proved to be the best strategy, with responses between 30% and 45% [2,[36][37][38].…”
Section: Post-transplant Treatmentmentioning
confidence: 99%
“…In uncontrolled studies the combined use of pegylated interferon and ribavirin proved to be the best strategy, with responses between 30% and 45% [2,[36][37][38].…”
Section: Post-transplant Treatmentmentioning
confidence: 99%
“…[93][94][95][96]100,101,104,105 A meta-analysis from over 40 treatment trials estimated that SVR rates of combination therapy were 24% and 27%. 147 A recent systematic review of predominantly therapeutic intervention studies by Berenguer et al confirmed that 30.2% of patients treated with PEG-IFN plus ribavirin will attain SVR. 131 Dose reductions and discontinuation of treatment were common in these studies: 73% and 27.6%, respectively.…”
Section: Peg-ifn Plus Ribavirinmentioning
confidence: 99%
“…Combination therapy for HCV after liver transplantation is currently recommended, and the most widely used is pegylated-interferon (Peg-IFN) plus ribavirin. Treatment of HCV with Peg-IFN plus ribavirin after liver transplantation is generally only successful in achieving SVR in 20-45% of recipients and is associated with high rates (30-50%) of discontinuation due to intolerability (Ponziani et al, 2011;Wang et al, 2006). The inability to reach target RBV doses due to the high prevalence of renal insufficiency in recipients is a major limiting factor in achieving an acceptable SVR rate (Chalasani et al, 2005;Gane et al, 1998).…”
Section: Hepatitis C Virusmentioning
confidence: 99%